2014
DOI: 10.12693/aphyspola.126.751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature and Ambient on Formation, Composition and Bandgap of Cu_2ZnSnS_4 Thin Films

Abstract: Amorphous CuZnSnS precursor lms were prepared by solgel and spin-coating with copper chloride, zinc chloride, tin chloride and thiourea solutions as starting materials. A Cu2ZnSnS4 lm with kesterite structure and a small amount of chlorine formed when the precursor was annealed under Ar ambient at temperature above 200• C, but its atomic ratios of Cu:Zn:Sn:S far deviated from stoichiometric ratios of the Cu2ZnSnS4. However, when the precursor lms were annealed with sulfur powder together at temperatures betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The sputtering conditions are shown in Table I. Three kinds of precursor thin films were annealed with sulfur powder for 2 h, respectively, in a tubular furnace with two zones [6], where one zone was for laying the precursor thin film and the other was for laying S source. Both the sample temperature and S source temperature are 500 The microstructures of CZTS films were analyzed by X-ray diffraction (XRD, D/max 2500/PC, Cu K α , λ = 1.5406 Å) and the Raman spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…The sputtering conditions are shown in Table I. Three kinds of precursor thin films were annealed with sulfur powder for 2 h, respectively, in a tubular furnace with two zones [6], where one zone was for laying the precursor thin film and the other was for laying S source. Both the sample temperature and S source temperature are 500 The microstructures of CZTS films were analyzed by X-ray diffraction (XRD, D/max 2500/PC, Cu K α , λ = 1.5406 Å) and the Raman spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in contrast to crystalline materials with fixed stoichiometric ratio, chemical composition of amorphous materials can be adjusted in a broader range, which supports the active element enrichment within the amorphous shell. [ 22 ] However, the electronic conductivity and stability of the amorphous materials tend to downgrade due to the structural disorder and thermodynamic instability. [ 23 ] Crystalline materials typically exhibit better electrical conductivity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Recalling the previous work, the band gap energy has been influenced by the variation in grain size and stoichiometry of the films [24,[34][35][36][37][38], which mainly depends on the deposition speed of convective deposition and annealing temperature. Band gap energies of the CZTS films were determined by extrapolating the linear region of αhv 2 versus photon energy (hv) curve to the intercept of the photon energy axis of CZTS films deposited at different deposition speeds and annealing temperatures as shown in the Fig.…”
Section: Energy Band Gapmentioning
confidence: 64%
“…They reported that the band gap of CZTSe shifts to higher energies as Cu/(Zn+Sn) decreases [29] which refer to Cu-poor and Zn-rich conditions of CZTS films. Moreover, the energy band gap increases when the S content is decreased at higher annealing temperature [34]. As seen in Fig.…”
Section: Energy Band Gapmentioning
confidence: 76%